Efforts to Improve Student Learning Outcomes in Learning Time Measurement Materials Through the Use of Wall Clock Media - Fitri Ismayanti Sembiring; Siti Rofiah; Rora Rizki Wandini (Yayasan Zia Salsabila, 2022)
Expansion of results on learning materials to estimate time by involving hours media in class V SDN 106162 Medan Estate. This exploration aims to describe the learning outcomes of class V SDN 106162 Medan Estate using a wall clock. The testing technique used is an illustrative strategy with a collaborative framework between specialists, supervisors, and partners who are associated with a group of scientists. Based on the assessment of the progress of the surrogate value of the results on the extended cycle the surrogate study achieved yields from 60% to 75%, and the cycles went from 75% to 85.83%. This means that the watch media can build a side effect of concentrating on Class V SDN 106162 Medan Estate in learning mathematics on the subject of time measurement.